A revolt of the distrustful? Political trust, political protest and the democratic deficit - Edgar Grande; Daniel Saldivia Gonzatti (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2024)
During recent crises in Europe, new heterogeneous protest movements have emerged that are difficult to label and classify. Existing studies suggest that the common denominator of these protesters is primarily the lack of political trust. Therefore, these new protest movements offer favorable conditions for investigating the relationship between political trust and protest, and the consequences of political distrust for the stability of democracy. Do these protests represent a revolt of the distrustful which intensifies the frequently invoked crisis of democracy? Our study answers this question by focusing on two recent protest movements, the COVID-19 protest and the so-called 'energy protest', which have been an important part of the Ger-man protest landscape in recent years. Based on new survey data, our results reveal a considerable lack of trust in the core institutions of representative democracy in Germany and that political distrust increases the readiness for protest and the acceptance of political violence. The consequences of distrust for democracy are ambiguous, however. The distrustful citizens are strong supporters of direct democracy but hold illiberal and restrictive attitudes towards minorities and migrants. Hence, there are good reasons to be distrustful towards the distrustful citizens on the streets.
Keywords: 330; protest; political trust; political violence; democratic deficit; social movements